Analysis of the use of the Hashtag #JulidFiiSabilillah on Instagram in the Psychological role of the Attack on Palestine by Israel - Annisa Utami*; Muhammad Jailani (Universitas Syiah Kuala, 2024)
This study analyzes the use of the hashtag #JulidFiSabilillah on Instagram as a tool in the psychological warfare that occurred during the Israeli attack on Palestine. This research aims to find out how the hashtag affects public perceptions and emotions. Using a qualitative method with a case study approach, this study analyzed the top 30 contents that used the hashtag. The results showed that the hashtag #JulidFiSabilillah was used in various themes such as solidarity, activism, emotional, attack, and information. Content with attack and information themes is more dominant and gets high interaction, indicating that this hashtag is effective in shaping public opinion and influencing people's emotions. Content with emotional themes also shows a significant influence in generating empathy for Palestine. This research shows that social media, particularly through the use of hashtags, can play an important role in psychological warfare by changing people's perceptions and emotions